Ileocecal intussusception as presentation for ascending colon carcinoma. Case report - Domínguez Páez, Casandra; Salazar Andrade, Jorge Alberto; Mendoza Tagle, Dafne Ivonne; Martín Pérez, Jesús Antonio; Rodriguez Pulido, Jorge Armando; Cortazar Sánchez, Carlos Arturo (International journal of surgery case reports, 2023)
Intussusception is described as invagination of a segment of the bowel into the lumen of an adjacent segment. Although it is the most frequent cause of intestine obstruction during childhood, it is unusual in adulthood, where intussusception represents 1% of all intestine obstructions and 5 % of all intussusceptions. A 64-year-old female presented with a history of weight loss, intermittent diarrhea, and occasional transrectal bleeding. An abdominal computed tomography (CT scan) was performed showing a neoproliferative appearance and associated intussusception of the ascending colon. Colonoscopy revealed an ileocecal intussusception and a tumor on the ascending colon. Right hemicolectomy was performed. Histopathological findings were consistent with colon adenocarcinoma. Adults have an organic lesion within the intussusception in up to 70 % of cases. The clinical presentation of intussusception can vary significantly between children and adults, who will often exhibit chronic nonspecific symptoms including nausea, changes in bowel habits, and gastrointestinal bleeding. The imaging diagnosis of intussusception is a difficult subject, the basis for the diagnosis is a high index of clinical suspicion and noninvasive techniques. Intussusception is an extremely rare condition in adults, in this age group, the malignant entity is one of the main etiologies. Intussusception continues to be a rare entity and should be considered as a differential diagnosis of chronic abdominal pain and intestinal motility disorders; the treatment of choice continues to be surgical.